PENGETAHUAN, PERSEPSI DAN PERILAKU MAHASISWA DALAM PEMBELIAN NADA SAMBUNG - Ardiansyah, Rheza; Djamaludin, Moh. Djemdjem; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2012)
The aim of this research was to analyze the knowledge, perception, and ring back tone’s purchasing behavior of college students. The research used cross-sectional design and conducted in Bogor Agricultural University. The amount of college students in this study was 36 of the first grade who activated ring back tone at the time when survey was held. Data were collected through filling in the questionnaire. The data were analyzed by descriptive statistic and multiple linear regression. Result showed that college student’s knowledge level about ring back tone was in high stage. Meanwhile, perception toward ring back tone was in a less agree level. College students had ring back tone’s purchasing behavior in moderate category. Regression analysis showed that ring back tone’s purchasing behavior of College students was influenced by their perception (p<0,01).